The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4172/2155-9600.1000629
|View full text |Cite
|
Sign up to set email alerts
|

Development of Probiotic Beverage from Whey and Orange Juice

Abstract: Probiotics are microorganisms that provide health benefits when consumed. The term probiotic is currently used to indicate the ingested microorganisms associated with beneficial effects to humans and animals. Probiotic drinks are typically dairy-based beverages with consistency similar to milk. They are consumed for digestive health. The addition of probiotics to whey will enhance the properties and benefits to several folds. Addition of orange juice gives it better sensory properties and mainly increases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is a source of proteins, which have the highest biologic value among all proteins present in food [126]. e uses of fermented whey and fruit beverages as a carrier for probiotic bacteria are the subject of a large number of publications in recent years [127,128]. Furthermore, adding whey to juice allowed enhancing the beneficial bacteria growth and increased the probiotic properties of the end products.…”
Section: Opportunities and Challenges For Functionalmentioning
confidence: 99%
“…It is a source of proteins, which have the highest biologic value among all proteins present in food [126]. e uses of fermented whey and fruit beverages as a carrier for probiotic bacteria are the subject of a large number of publications in recent years [127,128]. Furthermore, adding whey to juice allowed enhancing the beneficial bacteria growth and increased the probiotic properties of the end products.…”
Section: Opportunities and Challenges For Functionalmentioning
confidence: 99%
“…Nutritional value and the growing awareness of consuming food with health promoting additives qualify whey as a healthy functional food. Liquid fermented whey can be a carrier of probiotics with low cholesterol and lactose content, which is an appropriate beverage for most of the human population because 5-15% of European population and up to 80% of the population from central Asia and Africa are lactose intolerant (Shukla and Kushwaha, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the fermented whey using kefir grains has been investigated by different authors (Londero et al, 2011(Londero et al, , 2012Balabanova and Panayotov, 2011;Megalhães et al, 2011;Shukla and Kushwaha, 2017) indicating that fermented whey beverages can be interesting alternative for cheese whey utilization. Kefir grains are a symbiotic association of lactic acid bacteria, yeasts and acetic acid surrounded by kefiran, water soluble polysaccharide matrix (Megalhães et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been found that the use of whey in mixtures with low-cost raw materials and the application of a continuous process promote effectively its fermentation by kefir, leading to the potential production of novel alcoholic drinks (Reddy et al., 1987; Kourkoutas et al., 2002; Athanasiadis et al., 2002; Paraskevopoulou et al., 2003; Athanasiadis et al., 2004). Similarly, proviotic beverages were previously prepared by blending whey and orange or pineapple juice in different ratios using Lactobacillus acidophilus and/or Bifidobacterium bifidium for mixtures fermentation (Shukla et al., 2013; Shukla and Kushwaha, 2017). At the same time there is serious reducing of various agro-industrial wastes polluting the environment.…”
Section: Introductionmentioning
confidence: 99%